Genomic analysis of a functional haloacid-degrading gene of Bacillus megaterium strain BHS1 isolated from Blue Lake (Mavi Gölü, Turkey) - Abdul Wahhab, Batool Hazim; Samsulrizal, Nurul Hidayah; Edbeib, Mohamed Faraj; Abdul Wahab, Roswanira; Al-Nimer, Marwan S.M; Abdul Hamid, Azzmer Azzar; Oyewusi, Habeebat Adekilekun; Kaya, Yilmaz; Notarte, Kin Israel R.; Mohd Sharif, Amir Husni; Huyop, Fahrul Zaman (Springer Nature, 2021)
Purpose: Bacillus megaterium strain BHS1, isolated from an alkaline water sample taken from Mavi Gölü (Blue Lake, Turkey), can grow on minimal medium containing 2,2-dichloropropionic acid. We characterized this bacterium at the genomic level. Methods: The HiSeq platform was used to carry out genome sequencing, de novo assembly, and scaffolding with strain BHS1. Next, genome data were analyzed to demarcate DNA regions containing protein-coding genes and determine the function of certain BHS1 genes. Finally, results from a colorimetric chloride ion–release assay demonstrated that strain BHS1 produces dehalogenase. Results: De novo assembly of the BHS1 genomic sequence revealed a genome size of ~ 5.37 Mb with an average G+C content of 38%. The predicted nuclear genome harbors 5509 protein-coding genes, 1353 tRNA genes, 67 rRNA genes, and 6 non-coding (mRNA) genes. Genomic mapping of strain BHS1 revealed its amenability to synthesize two families of dehalogenases (Cof-type haloacid dehalogenase IIB family hydrolase and haloacid dehalogenase type II), suggesting that these enzymes can participate in the catabolism of halogenated organic acids. The mapping identified seven Na+ /H+ antiporter subunits that are vital for adaptation of the bacterium to an alkaline environment. Apart from a pairwise analysis to the well-established L-2-haloacid dehalogenases, whole-cell analysis strongly suggested that the haloacid dehalogenase type II might act stereospecifically on L-2-chloropropionic acid, D,L-2-chloropropionic acid, and 2,2-dichloropropionic acid. Whole-cell studies confirmed the utilization of these three substrates and the gene’s role in dehalogenation. Conclusions: To our knowledge, this is the first report of the full genome sequence for strain BHS1, which enabled the characterization of selected genes having specific metabolic activities and their roles in the biodegradation of halogenated compounds.